2016
DOI: 10.1590/1519-6984.22614
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of Beauveria spp. isolates to control the broad mite Polyphagotarsonemus latus (Banks, 1904) (Acari: Tarsonemidae)

Abstract: This study was performed under laboratory conditions to identify isolates of the fungus Beauveria spp. that can control Polyphagotarsonemus latus in the greenhouse and field. Thirty Beauveria spp. isolates were tested by spraying 1 mL conidia (1 × 10 8 conidia/mL) on pepper leaf discs containing 15 mites. Evaluations were performed on the 3rd and 6th day post application by counting the number of dead mites. Vegetative growth and conidial production were measured from the selected isolates, and bioassays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Spons dilapisi dengan tisu yang dibasahi, selanjutnya daun jeruk diletakkan di atas kapas dengan permukaan abaksial menghadap atas. Kemudian daun dilapisi dengan tisu yang sudah dilubangi pada bagian daun (Martins et al 2016). Untuk mencegah kekeringan pada spons dan menjaga kondisi daun dalam keadaan turgid, dilakukan penyiraman dua hari sekali pada cawan petri (Puspitarini et al 2021a).…”
Section: Perbanyakan Tungauunclassified
See 1 more Smart Citation
“…Spons dilapisi dengan tisu yang dibasahi, selanjutnya daun jeruk diletakkan di atas kapas dengan permukaan abaksial menghadap atas. Kemudian daun dilapisi dengan tisu yang sudah dilubangi pada bagian daun (Martins et al 2016). Untuk mencegah kekeringan pada spons dan menjaga kondisi daun dalam keadaan turgid, dilakukan penyiraman dua hari sekali pada cawan petri (Puspitarini et al 2021a).…”
Section: Perbanyakan Tungauunclassified
“…Pada tanaman yang terinfestasi, TPJ sebagian besar memakan bagian apikal tanaman (Rosado et al 2014) dan memecahkan dinding sel tanaman dengan chelicerae-nya (Jeppson et al 1975;Zhang 2003), yang mengakibatkan kebocoran konten intraseluler (Martins et al 2016). Perubahan morfofisiologis tanaman yang disebabkan oleh TPJ akan menyebabkan terhambatnya pertumbuhan tanaman, bunga dan buah rontok, juga penolakan oleh konsumen karena kerusakan, seperti distorsi daun, perubahan warna bunga, dan buah melepuh (Gerson 1992;Grinberg et al 2005;Sarmento et al 2011).…”
Section: Pembahasanunclassified
“…To make an arena, a water-soaked sponge (5 cm x 5 cm x 1.5 cm) was placed inside a Petri dish (d = 9 cm). The sponge was covered with moistened cotton, and then, a citrus leaf was placed over the cotton with the abaxial surface facing up (Martins et al 2016). Regular watering was done to maintain the humidity in Petri dishes, keep the leaf in turgid condition, and prevent the desiccation of the mites (Puspitarini et al 2021).…”
Section: Mite Rearingmentioning
confidence: 99%
“…Thereafter, mites that emerged on the same day were taken for the experiment. Following the treatments, mortality was checked daily during 6 days of the observation period (Martins et al 2016). Test mites were assumed dead if there was no movement of the appendages when being touched with a brush.…”
Section: Fungal Pathogenicity Assay Against P Latusmentioning
confidence: 99%
“…A major consideration in the development of entomopathogenic fungi for biological control is the selection of the most virulent strains against the target pest [5]. Abadias et al [6] suggested that, for a fungal biocontrol agent to be suitable for use under field conditions, it is important that the inoculum has necessary ecological fitness to withstand abiotic interactions in form of natural fluctuations in temperature and relative humidity.…”
Section: Introductionmentioning
confidence: 99%